2016
DOI: 10.1002/14651858.cd012067.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive positive pressure ventilation for acute asthma in children

Abstract: Current evidence does not permit confirmation or rejection of the effects of NPPV for acute asthma in children. Large RCTs with low risk of bias are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 90 publications
0
23
0
2
Order By: Relevance
“…This highlights the diagnostic difficulties in separating severe acute asthma from viral pneumonia in some of the cases. Current evidence does not support any positive outcome effects of noninvasive positive pressure ventilation for treatment of children with acute asthma other than symptom relief and decrease of work of breathing ( 11 ). It is still widely used, however, across ICUs worldwide, and our pathway also includes this mode of support early in the management of severe acute asthma.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the diagnostic difficulties in separating severe acute asthma from viral pneumonia in some of the cases. Current evidence does not support any positive outcome effects of noninvasive positive pressure ventilation for treatment of children with acute asthma other than symptom relief and decrease of work of breathing ( 11 ). It is still widely used, however, across ICUs worldwide, and our pathway also includes this mode of support early in the management of severe acute asthma.…”
Section: Discussionmentioning
confidence: 99%
“…A 2016 Cochrane review concluded that the available evidence at the time was insufficient to evaluate the effect of NIV on asthma exacerbations in children and that better designed studies with larger samples size are required. 16 Anecdotal evidence suggests that NIV in asthma exacerbations may help to avoid or delay endotracheal intubation in children with severe exacerbations, with impending respiratory failure. Endotracheal intubation and invasive mechanical ventilation in these patients is associated with important morbidity such as barotrauma, hemodynamic instability, infections and an increased length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical findings are wheezing, shortness of breath, chest tightness and cough with variable expiratory airflow limitation. Regular controller therapy is required to achieve symptom control and avoid respiratory morbidity such as exacerbations ( 18 , 19 ).…”
Section: Asthmamentioning
confidence: 99%
“…Based on this physiologic rationale, there are several studies on the NIV use for children with acute asthma exacerbations. A recent Cochrane review included the following two studies on the use of NIV in children with acute asthma exacerbation ( 19 ). Thill et al studied the effect of NIV among 20 children with acute asthma exacerbation who were admitted to the pediatric intensive care unit (ICU) in a prospective cross-over study.…”
Section: Asthmamentioning
confidence: 99%